Into these knots : poems - McHugh, Ashley Anna (Ivan R. Dee, 2010)
The poems of Into These Knots, Ashley Anna McHugh's debut collection, glance from heaven to earth, from earth to heaven, interrogating and elucidating in elegant and supercharged speech ultimate questions and intimate foibles. With equal parts intelligence and passion, Ms. McHugh can quarrel with scripture or riff on the amorous pleadings of Andrew Marvell or the stark musings of Baudelaire. Ms. McHugh's poems resound with a songlike intensity and an arresting power entirely their own. Personal meditations on loss, and the need to reconcile with the past, ground this collection, even as the po.